La heredad de la Zarzuela. Nuevos documentos de su historia - Toajas Roger, Mª Ángeles (Anales de Historia del Arte, 2007)
Contribution of primary sources for the history of the Royal Site of La Zarzuela from the end of 15th century until 1625, when this agricultural estate was bought by Cardenal Infante Fernando de Austria and then used by his brother, king Felipe IV, as a rural retreat for his private pleasure. New knowledge about this manor along the 16th century, on its characteristics and owners, first a madrilenian family Córdoba Sotomayor and, from 1525 onwards, Alonso Gutiérrez de Madrid and his descendants.